What should a ‘gold standard’ balanced communications and engagement scorecard look like for the Nottingham University Hospitals? - Kuffer, Ariane / AK (2009)
The project presented in this report was carried out under a mandate given by Ms Cath Lovatt, Director of the Directorate of Communications and Marketing at the Nottingham University Hospitals (NUH), the fourth largest acute teaching trust in the UK. It aimed at using the balanced scorecard approach to evaluate how the Directorate could assess its progress towards its strategic objectives. The 12-week consultancy project was guided by the research question “What should a ‘gold standard’ balanced communications and engagement scorecard look like for the NUH?”